Awareness about the carcinoma breast and the practices related to self- breast examination among women in developing countries - ., Shipra; Kumari, Reema; Singh, G. N. (International Journal Of Community Medicine And Public Health, 2021)
The aim of this review article was to evaluate the awareness of carcinoma breast and practices related to self- breast examination among women in developing countries. The study included the exploration of databases and journal websites, pub med, google scholar, and medline. The articles studied for the review were focused on english language articles from the year 2013 to 2019. This review focused on knowledge of breast cancer and its risk factors among women. Fifteen articles were reviewed on this topic from the year 2013 to 2019 in which general awareness level of breast cancer was probably better than the knowledge of risk factor, sign and symptoms. It also shows that although awareness and knowledge regarding Breast cancer was satisfactory but the knowledge of self-breast examination was low and practice of self-breast examination was least in developing countries. So, awareness programs related to breast cancer should be planned, to ensure early detection and timely treatment for better outcome.